Detection of throwing in cricket using wearable sensors - Wixted, A.; Portus, M.; Spratford, W.; James, D. (Sports Technology, 2011)
One of the great controversies of the modern game of cricket is the determination of whether a bowler is using an illegal throw-like bowling action. Changes to the rules of cricket have reduced some of the confusion; yet, because of the complexities of the biomechanics of the arm, it is difficult for an umpire to make a judgement on this issue. Expensive laboratory-based testing has been able to quantify the action of a bowler and this testing is routinely used by cricket authorities to assess a bowling action. Detractors of the method suggest that it is unable to replicate match conditions, has long lead times for assessment and is only available to the elite. After extensive laboratory validation, we present a technology and method for an in-game assessment using a wearable arm sensor for differentiating between a legal bowling action and throwing. The method uses inertial sensors on the upper and lower arms that do not impede the bowling action. Suspect deliveries, as assessed by an expert biomechanist using high-speed video and motion capture, reveal valid distinctive inertial signatures. The technology is an important step in the monitoring of bowling action on-field in near real-time. The technology is suitable for use in competition as well as a training tool for developing athletes.